Introducing the CONSORT extension to pilot trials: Enhancing the design, conduct and reporting of pilot or feasibility trials - Abbade, Luciana P.F. [UNESP]; Abbade, Joelcio F. [UNESP]; Thabane, Lehana (Springer Nature, 2018)
This editorial provides a brief overview of the importance of pilot or feasibility trials or studies, the challenges with current practices in their conduct and reporting, an introduction to the Consolidated Standards of Reporting Trials (CONSORT) extension to pilot trials aimed at improving their reporting, along with some key resources on aspects related to pilot and feasibility studies.